Preparation method of asphalt-based sodium ion battery hard carbon negative electrode material

Through segmentation reducing technology, improve the orderly and electrochemical properties of asphalt -based hard carbon materials, solve the problem of low sodium storage capacity and insufficient circulation stability of sodium ion battery, and achieve efficient, environmental protection and economy Sodium ion battery performance improves.

CN119330336AActive Publication Date: 2025-01-21INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411489118.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

In the prior art, asphalt-based hard carbon materials face problems such as low sodium storage capacity, low ICE and low platform capacity when used in the negative electrode of sodium ion battery.

Method used

Through segmented polycondensation of asphalt, hydrogenation polycondensation is performed first, and then catalytic polycondensation is performed to control the polycondensation conditions and improve the structural order and electrochemical performance of hard carbon materials.

Benefits of technology

It significantly improves the charging and discharge efficiency and cycle stability of sodium ion batteries, while at the same time, it has the characteristics of high cost benefits and environment -friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330336A_ABST
    Figure CN119330336A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an asphalt-based sodium-ion battery hard carbon negative electrode material, which comprises the following steps: (S1) sequentially carrying out hydrogenation polycondensation and catalytic polycondensation on asphalt substances to obtain a precursor; (S2) carrying out acid pickling, water washing and drying on the precursor, and then carrying out oxidation treatment to obtain an oxidized precursor; (S3) carrying out medium-temperature pre-carbonization treatment on the oxidized precursor in an inert atmosphere; and (S4) carrying out high-temperature carbonization on the pre-carbonized material obtained in the step (S3) in an inert atmosphere or a hydrocarbon gas atmosphere to obtain the hard carbon material. The asphalt-based hard carbon material disclosed by the invention shows excellent electrochemical performance, and has higher sodium storage capacity and good cycling stability. The preparation method is simple, low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for sodium ion batteries, and in particular relates to a method for preparing a hard carbon negative electrode material for an asphalt-based sodium ion battery. Background Art

[0002] In the context of the current energy and environmental crisis, the development of efficient and environmentally friendly energy storage technology has become one of the important directions of global scientific research. Lithium-ion batteries have become the darling of the market due to their superior energy density and long cycle life. However, due to the limited lithium resources and cost issues, researchers have begun to seek other sustainable alternatives, among which sodium-ion batteries have attracted widespread attention due to the abundance of sodium and low cost.

[0003] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Both batteries store and release energy by embedding and de-embedding ions in positive and negative electrode materials. However, the large ionic radius of sodium ions leads to poor embedding performance in traditional graphite negative electrode materials, which directly limits their energy density and cycle stability. Therefore, the development of new negative electrode materials suitable for sodium-ion batteries has become a research focus. As a non-graphitizing carbon material, hard carbon exhibits good storage capacity for sodium ions due to its unique pore structure and high specific surface area. The preparation of hard carbon usually comes from natural organic matter or artificial organic polymers, but these materials often have problems such as high cost and limited sources. Asphalt, as a widely available and inexpensive by-product of petroleum processing, provides an economically feasible hard carbon precursor option. Through appropriate heat treatment, asphalt can be converted into structurally stable hard carbon for use as a negative electrode material for sodium-ion batteries.

[0004] However, the development of asphalt-based hard carbon is not without challenges. First, the composition of asphalt is complex, and the properties of asphalt from different sources may vary greatly, which puts forward requirements for its consistency and performance stability as a battery material. Second, in the preparation process of hard carbon, how to control the pyrolysis temperature and atmosphere to optimize the microstructure and electrochemical properties of hard carbon is also a technical difficulty.

[0005] CN118545701A discloses a method for preparing asphalt-based hard carbon, wherein asphalt powder is pre-oxidized and carbonized at high temperature in sequence to obtain the asphalt-based hard carbon; the pre-oxidation comprises: laying the asphalt powder in a carrier with a thickness of 0.2 to 2 cm, and heat treating it in an oxygen-containing atmosphere at 150 to 350°C for 2 to 12 hours.

[0006] CN118239467A discloses an asphalt-based hard carbon material for a negative electrode of a sodium ion battery, and its preparation method is as follows: (1) under the protection of an inert gas, oxidized asphalt, a cross-linking agent and a catalyst are mixed, heated with stirring, reacted, and cooled to room temperature after the reaction is completed; (2) the product of step (1) is placed in a coking furnace, first solidified under an inert atmosphere, then coked, and then the pre-carbonized precursor is crushed to obtain a carbon material precursor powder; (3) the carbon material precursor powder of step (2) is subjected to a high-temperature carbonization treatment under an inert atmosphere to obtain a carbon negative electrode material for a sodium ion battery.

[0007] CN117776156A discloses a technology for preparing asphalt-based hard carbon negative electrode, which includes the following steps: S1, softening of solid asphalt: heating solid asphalt at normal pressure to obtain softened asphalt; S2, oxidation reaction of softened asphalt: in an oxygen atmosphere, performing negative pressure heating and negative pressure insulation operations on the softened asphalt in turn to obtain a hard carbon precursor; S3, carbonization of the hard carbon precursor: in an inert gas atmosphere, performing high-temperature carbonization operations on the hard carbon precursor to obtain a carbonized material; S4, crushing of the carbonized material: cooling and crushing the carbonized material in turn to obtain the final asphalt-based hard carbon.

[0008] The above patent discloses the steps of softening and / or oxidizing asphalt, but current technology makes it difficult to fully condense small molecule asphalt into large molecules or even more effective polymers, resulting in molecular rearrangement and reorganization in the subsequent carbonization process, causing the carbonized product to have a high degree of graphitization, and therefore the electrochemical performance is not excellent enough. Summary of the invention

[0009] In view of the problems of low sodium storage capacity, low ICE and low platform capacity faced by asphalt-based hard carbon materials in the prior art when used for the negative electrode of sodium ion batteries, the present invention provides a high-performance asphalt-based hard carbon negative electrode material for sodium ion batteries. The present invention polycondenses the asphalt in stages, first performing hydrogenation polycondensation and then catalytic polycondensation. By controlling the polycondensation conditions, the structural orderliness and electrochemical properties of the hard carbon material are effectively improved. It not only improves the charge and discharge efficiency and cycle stability of sodium ion batteries, but also has the characteristics of high cost-effectiveness and environmental friendliness, providing new possibilities for the commercial application of sodium ion batteries.

[0010] The purpose of the present invention is achieved through the following technical solutions:

[0011] A method for preparing a pitch-based sodium ion battery hard carbon negative electrode material comprises the following steps:

[0012] (S1) subjecting the asphalt-based material to hydrogenation polycondensation and catalytic polycondensation in sequence to obtain a precursor;

[0013] (S2) acid-washing, water-washing, drying, and then oxidizing the precursor to obtain an oxidized precursor;

[0014] (S3) the oxidized precursor is subjected to a medium temperature pre-carbonization treatment under an inert atmosphere;

[0015] (S4) Carbonizing the pre-carbonized material in step (S3) at high temperature in an inert atmosphere or a hydrocarbon gas atmosphere to obtain a hard carbon material.

[0016] The prior art pre-oxidizes asphalt-based hard carbon materials with oxygen or other oxidants in the hope of improving the sodium storage performance of the material. However, even after high oxidation, only the oxygen content of the asphalt can be changed, and other structural characteristics of the asphalt molecules are not changed, so the effect on improving the sodium storage performance is limited. To the surprise of the inventors, the electrochemical properties of the asphalt-based hard carbon negative electrode materials can be significantly optimized by increasing the softening point of the asphalt through a two-stage polycondensation method. However, the order of the two-stage polycondensation cannot be reversed, nor can it be combined into a one-step synchronous polycondensation, otherwise the intended purpose, that is, the purpose of significantly improving the electrochemical performance of the carbon negative electrode material, cannot be achieved. Because after hydrogenation, it is easier to polymerize small molecules of asphalt into larger molecules, and it is easier to avoid the subsequent rearrangement of carbon atoms in the chemical bonds, and the strength between the molecules of the prepared hard carbon material is made higher, which is more conducive to obtaining a closed-pore structure that is conducive to sodium storage.

[0017] Furthermore, in step (S1), the asphalt material is selected from coal-based asphalt, petroleum asphalt, petroleum heavy oil and biomass asphalt, as well as petroleum heavy oil, naphthalene, anthracene and other aromatic hydrocarbons, and the softening point of the asphalt material is between 60°C and 130°C.

[0018] Furthermore, in step (S1), the hydrogenated polycondensation is to mix the asphalt material and the hydrogen donor evenly, heat to 350-450°C, the hydrogenated polycondensation pressure is 1-2MPa, and the hydrogenated polycondensation time is 3-5h; the catalytic polycondensation is to mix the hydrogenated polycondensation product and the Lewis acid catalyst evenly, carry out catalytic polycondensation at 200-300°C, the catalytic polycondensation pressure is 2-4MPa, and the catalytic polycondensation reaction time is 1-2h.

[0019] Furthermore, in step (S1), the mass ratio of the asphalt material, the hydrogen donor and the catalyst is 100:5-10:1-3. Furthermore, the hydrogen donor includes but is not limited to at least one of polyethylene, polypropylene and polystyrene; and the Lewis acid catalyst is selected from at least one of AlCl3, HF-BF3 and FeCl3.

[0020] Furthermore, the molecular weight of the polyolefin is 700,000 to 1,000,000. The inventors found that the use of high molecular weight polyethylene as a hydrogen donor has the best effect. The possible reason is that the entanglement of high molecular weight ultra-long molecular chains can easily prevent the precipitation of H atoms, and then they are easily absorbed by asphalt molecules. However, the molecular weight of polyolefin should not be too large, otherwise the polymer viscosity will be high, which will cause the asphalt to be unable to fully mix with it, and it will not be able to achieve the effect of stable hydrogen supply.

[0021] In the present invention, there is no particular limitation on the method for uniformly mixing the materials, including but not limited to ball milling, high-speed stirring, grinding, sand milling, etc.

[0022] Furthermore, in step (S2), the acid washing is to immerse the precursor in dilute hydrochloric acid to remove the added Lewis acid metal residues. The water washing is to wash with deionized water until it is neutral.

[0023] Further, in step (S2), the oxidant is one or a mixture of oxygen, ozone, potassium permanganate, potassium nitrate, sulfuric acid, nitric acid, and ferric oxide. Depending on the selected oxidant, the oxidation method also needs to be adjusted accordingly, such as using ozone and oxygen for oxidation treatment, using a heating and ventilation method; using sulfuric acid and nitric acid for oxidation, using an oxidation method in the liquid phase; using ferric oxide as an oxidant, using a solid phase mixed heating method.

[0024] Furthermore, in step (S2), when the heating and ventilation method is adopted, the temperature is raised to 250-350°C at a heating rate of 2-10°C / min and kept warm for 5-20 hours; when the liquid phase oxidation method is adopted, the asphalt is ground and then immersed in an oxidant solution for oxidation for 4-20 hours. The concentration of the oxidant is 1mol / L-8mol / L; when ferric oxide is used as the oxidant, the asphalt is mixed with ferric oxide, the amount of ferric oxide is 0.2-0.5 times the mass of the asphalt, and the temperature is raised to 250-350°C at a heating rate of 2-10°C / min and kept warm for 5-20 hours.

[0025] Furthermore, in step (S3), the medium temperature pre-carbonization treatment is carried out by heating the temperature to 500-800°C at a heating rate of 5-30°C / min and keeping the temperature for 2-5h, and the inert atmosphere is at least one of argon, helium and nitrogen. The purpose of pre-carbonization is to promote molecular cross-linking of the asphalt and obtain pre-carbonized material.

[0026] Furthermore, in step (S4), the inert atmosphere is at least one of argon, nitrogen, helium, radon, etc.; the hydrocarbon gas is at least one of methane, ethane, propane, butane, ethylene, acetylene, and toluene. Calcination in a hydrocarbon gas atmosphere is preferred, which is beneficial to further improve the initial efficiency and capacity of the hard carbon material.

[0027] Furthermore, in step (S4), the high temperature carbonization is carried out by heating the temperature to 1300-1600°C at a heating rate of 5-10°C / min and calcining the temperature for 5-10 hours. The heating rate is relatively fast during the pre-carbonization in step (S3), which is beneficial to avoid melting of the asphalt. It also avoids the rearrangement of molecules into soft carbon with a high degree of crystallization, which is beneficial to the storage of sodium ions and is beneficial to improving the material capacity.

[0028] The present invention uses asphalt, which has obvious cost advantages and mature technology, as the key raw material, and optimizes the molecular structure of the asphalt precursor through two-step polycondensation and pre-oxidation, effectively improving the sodium storage efficiency and initial coulomb efficiency of hard carbon. This preparation method is low-cost, high-efficiency, easy to operate, and is very suitable for large-scale production of hard carbon materials, and then used as the negative electrode material of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a SEM image of the hard carbon material obtained in Example 1.

[0030] Figure 2 This is the TEM image of the hard carbon material obtained in Example 1.

[0031] Figure 3 It is a constant current charge and discharge curve diagram of the hard carbon material obtained in Example 1.

[0032] Figure 4 This is a cycle curve diagram of the hard carbon material obtained in Example 1.

[0033] Figure 5 This is the SEM image of the hard carbon material obtained in Example 1.

[0034] Figure 6 This is the SEM image of the hard carbon material obtained in Comparative Example 2. DETAILED DESCRIPTION

[0035] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.

[0036] Example 1

[0037] (S1) 10 kg of coal-based asphalt with a softening point of 60° C. and 1 kg of polyethylene with a molecular weight of about 1 million are mixed uniformly by ball milling, the ball mill speed is 500 rpm, the ball-to-material ratio is 20:1, and the ball milling time is 5 h. The resulting mixture is placed in a reactor, and under the protection of an argon atmosphere, the temperature is increased to 400° C. at a heating rate of 5° C. / min and kept warm for 3 h at a pressure of 2 MPa, and then naturally cooled to room temperature; the resulting material and 0.3 kg of aluminum trichloride are mixed uniformly by ball milling, the ball mill speed is 500 rpm, the ball-to-material ratio is 20:1, and the ball milling time is 5 h. The resulting mixture is placed in a reactor again, and under the protection of an argon atmosphere, the temperature is increased to 240° C. at a heating rate of 5° C. / min and kept warm for 1 h at a pressure of 3 MPa to obtain a precursor.

[0038] (S2) The precursor obtained in step (S1) is immersed in dilute hydrochloric acid, stirred for 10 minutes, taken out, and repeatedly washed with deionized water until the effluent is neutral. The washed precursor is then dried and placed in a muffle furnace, heated in air at a heating rate of 5°C / min, a heating temperature of 300°C, and a holding time of 20 hours. After cooling, a pre-oxidized precursor is obtained.

[0039] (S3) Grinding the pre-oxidized precursor in step (S2) into powder, and then calcining it in a tubular furnace at a heating rate of 5°C / min, heating to 700°C and keeping the temperature for 3 hours in an Ar gas atmosphere to obtain a pre-carbonized material.

[0040] (S4) Grind the pre-carbonized material obtained in step (S3) into fine powder, place it in a high-temperature tubular furnace, introduce argon gas, and calcine it in an argon gas atmosphere at a heating rate of 5°C / min. After heating to 1300°C, keep the temperature for 3 hours, and cool it to room temperature to obtain a hard carbon negative electrode material.

[0041] from Figure 1 It can be seen that the hard carbon material prepared in Example 1 has a smooth and compact surface. Figure 2 The TEM photos show that in the process of preparing hard carbon materials, prepolymerization and oxidation significantly affect the material structure, forming interconnected closed pores. This is mainly because the high softening point asphalt has a longer molecular chain and a higher degree of cross-linking, and oxidation avoids the random bending of macromolecules at high temperatures, which ultimately makes it easier for macromolecules to form closed pores during the stacking process. In addition, the high oxygen content prevents the fusion of aromatic rings and the rearrangement of molecules during the pre-carbonization stage; at the same time, during the carbonization process, oxygen atoms and their nearby carbon atoms are removed, which also triggers the formation of defects and closed pores. This closed-pore structure helps to form metallic sodium clusters inside the hard carbon, and the increase in interlayer spacing is conducive to the migration of sodium ions between layers. Figure 5 This is the SEM image of the hard carbon material obtained in Example 1. Figure 6 This is the SEM image of the hard carbon material obtained in Example 2. Figure 5 , Figure 6 The hard carbon materials obtained by hydrogenation or catalytic condensation alone present a relatively regular layered structure, which cannot provide sufficient space to support effective sodium storage.

[0042] Example 2

[0043] Other conditions and operations are the same as those in Example 1, except that in step (S1), heavy petroleum oil is used as raw material instead of coal-based asphalt.

[0044] Example 3

[0045] Other conditions and operations are the same as those in Example 1, except that in step (S1), the molecular weight of the polyethylene is 700,000.

[0046] Example 4

[0047] Other conditions and operations are the same as those in Example 1, except that in step (S1), the molecular weight of the polyethylene is 500,000.

[0048] Example 5

[0049] Other conditions and operations are the same as those in Example 1, except that in step (S1), the molecular weight of the polyethylene is 1.5 million.

[0050] Example 6

[0051] Other conditions and operations are the same as those in Example 1, except that step (S2) is changed to: immersing the precursor obtained in step (S1) in 3 times the mass of 1 mol / L nitric acid and oxidizing for 15 h.

[0052] Example 7

[0053] Other conditions and operations are the same as those in Example 1, except that in step (S1), 0.3 kg of aluminum chloride is replaced by 0.2 kg of HF-BF3

[0054] Comparative Example 1

[0055] Other conditions and operations are the same as those in Example 1, except that step (S1) is changed to: 10 kg of coal-based asphalt with a softening point of 60°C and 1 kg of polyethylene with a molecular weight of about 1 million are uniformly mixed by ball milling, the ball mill speed is 500 rpm, the ball-to-material ratio is 20:1, and the ball milling time is 5 hours. The obtained mixture is placed in a reactor, and under the protection of an argon atmosphere, the temperature is increased to 400°C at a heating rate of 5°C / min and kept at a pressure of 2MPa for 3 hours, and naturally cooled to room temperature to obtain a precursor. That is, the step of catalytic polycondensation is omitted.

[0056] Comparative Example 2

[0057] Other conditions and operations are the same as those in Example 1, except that step (S1) is changed to: 10 kg of coal-based pitch with a softening point of 60°C and 0.3 kg of aluminum trichloride are uniformly mixed by ball milling, the ball mill speed is 500 rpm, the ball-to-material ratio is 20:1, and the ball milling time is 5 hours. The obtained mixture is placed in a reactor again, and the temperature is increased to 240°C at a heating rate of 5°C / min under the protection of an argon atmosphere, and the temperature is kept at 4 MPa for 1 hour to obtain a precursor. That is, the step of hydrogenation polycondensation is omitted.

[0058] Comparative Example 3

[0059] Other conditions and operations are the same as those in Example 1, except that step (S1) is changed to: 10 kg of coal-based asphalt with a softening point of 60°C and 0.3 kg of aluminum trichloride are mixed uniformly by ball milling, the ball mill speed is 500 rpm, the ball-to-material ratio is 20:1, and the ball milling time is 5 hours. The obtained mixture is placed in a reactor again, and under the protection of an argon atmosphere, the temperature is increased to 240°C at a heating rate of 5°C / min, and the mixture is kept warm for 1 hour at a pressure of 4 MPa; after cooling to room temperature, the obtained material and 1 kg of polyethylene with a molecular weight of about 1 million are mixed uniformly by ball milling, the ball mill speed is 500 rpm, the ball-to-material ratio is 20:1, and the ball milling time is 5 hours. The obtained mixture is placed in a reactor, and under the protection of an argon atmosphere, the temperature is increased to 400°C at a heating rate of 5°C / min and the mixture is kept warm for 3 hours at a pressure of 2 MPa, and the mixture is naturally cooled to room temperature to obtain a precursor. That is, the order of hydrogenation polycondensation and catalytic polycondensation is switched.

[0060] Comparative Example 4

[0061] Other conditions and operations are the same as those in Example 1, except that step (S1) is changed to: 10 kg of coal-based asphalt with a softening point of 60°C, 1 kg of polyethylene with a molecular weight of about 1 million, and 0.3 kg of aluminum trichloride are mixed uniformly by ball milling, the ball mill speed is 500 rpm, the ball-to-material ratio is 20:1, and the ball milling time is 5 hours. The obtained mixture is placed in a reactor again, and under the protection of an argon atmosphere, the temperature is increased to 400°C at a heating rate of 5°C / min, and the temperature is kept at a pressure of 2MPa for 3 hours, and the precursor is naturally cooled to room temperature. That is, hydrogenation polycondensation and catalytic polycondensation are carried out simultaneously.

[0062] Comparative Example 5

[0063] The other conditions and operations are the same as those in Example 1, except that step (S1) is changed to: placing coal-based pitch with a softening point of 60°C in a reaction kettle, and then heating to 400°C at a rate of 5°C / min under the protection of an argon atmosphere and under stirring, and then naturally cooling to room temperature after keeping the temperature for 5 hours to obtain a precursor. That is, Comparative Example 5 adopts a conventional heating softening process.

[0064] Application Examples

[0065] The method for preparing and testing the negative electrode material is as follows: the hard carbon obtained in the embodiment and the control experiment is used as the negative electrode material, and it is mixed with Super P and the binder CMC / SBR in a ratio of 94:2:4, and an appropriate amount of water is added for stirring to obtain a uniform electrode slurry; then the slurry is evenly coated on the copper foil, and cut after vacuum drying for 12 hours at 60°C. Sodium metal is used as the counter electrode, glass fiber is used as the separator, and 1 mol / L NaPF6 (dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) is used as the electrolyte, and a button-type battery is assembled in an argon environment glove box. Subsequently, a constant current charge and discharge experiment is carried out, the current density is set to 20mA / g, the voltage range is set to 0.001-2.0V, and the experimental results are recorded in Table 1.

[0066] Figure 3 is a constant current charge and discharge curve diagram of the hard carbon material obtained in Example 1; Figure 4 This is a cycle curve diagram of the hard carbon material obtained in Example 1.

[0067] Table 1 Electrochemical performance test of asphalt-based hard carbon negative electrode materials

[0068]

[0069] It can be seen from the half-cell test results of each embodiment in Table 1 that during the preparation process, after increasing the softening point of the asphalt-based precursor and fully oxidizing it, the capacity, first coulombic efficiency and cycle stability of the obtained hard carbon sample are significantly improved.

Claims

1. A method for preparing a pitch-based sodium ion battery hard carbon negative electrode material, characterized in that: The following steps are involved: (S1) subjecting the asphalt-based material to hydrogenation polycondensation and catalytic polycondensation in sequence to obtain a precursor; (S2) acid-washing, water-washing, drying, and then oxidizing the precursor to obtain an oxidized precursor; (S3) the oxidized precursor is subjected to a medium temperature pre-carbonization treatment under an inert atmosphere; (S4) Carbonizing the pre-carbonized material in step (S3) at high temperature in an inert atmosphere or a hydrocarbon gas atmosphere to obtain a hard carbon material.

2. The preparation method according to claim 1, characterized in that: In step (S1), the asphalt material is selected from coal-based asphalt, petroleum asphalt, petroleum heavy oil and biomass asphalt, as well as petroleum heavy oil, naphthalene, anthracene and other aromatic hydrocarbons, and the softening point of the asphalt material is between 60°C and 130°C.

3. The preparation method according to claim 1, characterized in that: In step (S1), the hydrogenation polycondensation is to mix the asphalt material and the hydrogen donor evenly, heat to 350-450°C, the hydrogenation polycondensation pressure is 1-2MPa, and the hydrogenation polycondensation time is 3-5h; the catalytic polycondensation is to mix the hydrogenation polycondensation product and the Lewis acid catalyst evenly, carry out catalytic polycondensation at 200-300°C, the catalytic polycondensation pressure is 2-4MPa, and the catalytic polycondensation reaction time is 1-2h.

4. The preparation method according to claim 1, characterized in that: In step (S1), the mass ratio of the asphalt material, the hydrogen donor and the catalyst is 100:5-10:1-3.

5. The preparation method according to claim 1, characterized in that: The hydrogen donor is a polyolefin, including but not limited to at least one of polyethylene, polypropylene, and polystyrene; the Lewis acid catalyst is selected from at least one of AlCl3, HF-BF3, and FeCl3.

6. The preparation method according to claim 5, characterized in that: The molecular weight of the polyolefin is 700,000 to 1,000,000.

7. The preparation method according to claim 1, characterized in that: In step (S2), the oxidant is one or a mixture of oxygen, ozone, potassium permanganate, potassium nitrate, sulfuric acid, nitric acid, and ferric oxide; Furthermore, depending on the selected oxidant, when ozone and oxygen are used for oxidation treatment, a heating and ventilation method is adopted; when sulfuric acid and nitric acid are used for oxidation, a liquid phase oxidation method is adopted; when ferric oxide is used as an oxidant, a solid phase mixed heating method is adopted; Furthermore, when the heating and ventilation method is used, the temperature is raised to 250-350°C at a rate of 2-10°C / min and kept warm for 5-20 hours; when the liquid phase oxidation method is used, the asphalt is ground and then immersed in an oxidant solution for oxidation for 4-20 hours. The concentration of the oxidant is 1mol / L-8mol / L; when ferric oxide is used as the oxidant, the asphalt is mixed with ferric oxide, the amount of ferric oxide is 0.2-0.5 times the mass of the asphalt, and the temperature is raised to 250-350°C at a rate of 2-10°C / min and kept warm for 5-20 hours.

8. The preparation method according to claim 1, characterized in that: In step (S3), the medium temperature pre-carbonization treatment is carried out by heating the temperature to 500-800°C at a heating rate of 5-30°C / min and keeping the temperature for 2-5h, and the inert atmosphere is at least one of argon, helium and nitrogen.

9. The preparation method according to claim 1, characterized in that: In step (S4), the inert atmosphere is at least one of argon, nitrogen, helium, radon, etc.; the hydrocarbon gas is at least one of methane, ethane, propane, butane, ethylene, acetylene, and toluene.

10. The preparation method according to claim 1, characterized in that: In step (S4), the high temperature carbonization is carried out by heating the temperature to 1300-1600°C at a heating rate of 5-10°C / min and calcining at this temperature for 5-10 hours.

Citation Information

Patent Citations

  • Preparation technology of pitch-based hard carbon negative electrode

    CN117776156A

  • Hard carbon negative electrode material prepared by pitch-based oxidation method and preparation method and application thereof

    CN115259135A

  • Method for preparing needle coke through composite modification of medium and low temperature coal tar pitch

    CN115521801A

  • Battery negative electrode hard carbon material and preparation method thereof

    CN116344804A

  • Preparation method of high-capacity asphalt-based hard carbon sodium ion battery negative electrode material

    CN116969442A

Cited By

  • Preparation method of modified asphalt-based hard carbon microspheres for negative electrode of sodium-ion battery

    CN120246986A

  • Preparation method and application of high-purity pitch-based hard carbon based on coal pitch polycondensation impurity removal

    CN120463183A